Percutaneous Transhepatic Biliary Interventions - Yadav, Ankusha; Condati, Naveen Kumar; Mukund, Amar (Journal of Clinical Interventional Radiology ISVIR, 2018)
Biliary tract interventions remain indispensable procedures for treatment of a wide arena of biliary tract pathologies. The increased use of endoscopic retrograde cholangiopancreatography (ERCP) for biliary tract evaluation and intervention has resulted in fewer patients requiring percutaneous transhepatic biliary interventions. However, there remains a subset of patients in whom ERCP is not feasible. Interventional radiologists play an important role in the management of biliary pathologies in such patients who cannot be benefited by endoscopic means. These interventions may at times be challenging; hence, awareness of normal and variant biliary tract anatomy and the variety of biliary tract interventions make the job easy. This article reviews the role of percutaneous transhepatic interventions in the management of a variety of biliary tract diseases, both benign and malignant, general indications and contraindications, preprocedural evaluation, and technical considerations specific to indications.
Keywords: biliary interventions; percutaneous transhepatic biliary drainage; biliary obstruction